Odpowiedź :
4y+2+2(2y²-3y-1-y²-8)=4y+2+4y²-6y-2-2y²-16=2y²-2y-16
w tym przykładzie jest błąd powinno być
4y+2+2(2y²-3y-1-y²-8)=4y+2+4y²-6y-2-2y²+16=2y²-2y+16
2(2y²-3y-1)-(4y+2)+y²+8=4y²-6y-2-4y-2+y²+8=5y²-10y+4
3(4y+2)-2(2y²-3y-1)-(y²+8)=12y+6-4y²+6y+2-y²-8=-5y²+18y
w tym przykładzie jest błąd powinno być
4y+2+2(2y²-3y-1-y²-8)=4y+2+4y²-6y-2-2y²+16=2y²-2y+16
2(2y²-3y-1)-(4y+2)+y²+8=4y²-6y-2-4y-2+y²+8=5y²-10y+4
3(4y+2)-2(2y²-3y-1)-(y²+8)=12y+6-4y²+6y+2-y²-8=-5y²+18y
a)
4y+2+2(2y (kwadrat)-3y-1-y(kwadrat)+8
4y+2+4y(kwadrat)-6y-2-2y(kwadrat)+16
2y(kwadrat)-2y+16
4y+2+2(2y (kwadrat)-3y-1-y(kwadrat)+8
4y+2+4y(kwadrat)-6y-2-2y(kwadrat)+16
2y(kwadrat)-2y+16
A+2(B-C)=
4y+2+2(2y^-3y-1-y^+8)=4y+2+2(4y^-3y-1-y^+8)=4y+2+8y^-6y-2-2y^+16=-2y+6y^+16
2B-A+C=
2(2y^-3y-1)-4y+2+y^+8=2y^-6y-2-4y+2+y^+8=3y^-10y+12
3A-2B-C=
3(4y+2)-2(2y^- 3y-1)-y^+8=12y+6-4y^+6y+2-y^+8=18y-5y^+16
^-To jest do kwadratu
4y+2+2(2y^-3y-1-y^+8)=4y+2+2(4y^-3y-1-y^+8)=4y+2+8y^-6y-2-2y^+16=-2y+6y^+16
2B-A+C=
2(2y^-3y-1)-4y+2+y^+8=2y^-6y-2-4y+2+y^+8=3y^-10y+12
3A-2B-C=
3(4y+2)-2(2y^- 3y-1)-y^+8=12y+6-4y^+6y+2-y^+8=18y-5y^+16
^-To jest do kwadratu